Gender, Culture and Environmental Conservation in Western Kenya: Contextualizing Community Participation and the Choice of Techniques (Nordic Journal of African Studies, 2000)
Despite the cross-cultural variations and the gradual but significant changes in gender roles and cultural systems that are found in Kenya today, there is no question that in many rural communities some tasks are still nearly always performed by men whereas others are predominantly the responsibility of women. This pattern is evident in the area of environmental conservation where the labour investment is still largely differentiated along gender lines. Although a great deal of attention has been paid to environmental protection in Kenya in recent years, the way a population exploits its habitat has a lot to do with the local circumstances and institutional norms, the cultural context, gender-power relationships within households and the material conditions of life. All these factors interact in complex ways to produce an overall pattern of gender division of labour, resource allocation and decision making in environmental management. Women in these cultures do not have a great deal of control in making major decisions about suitable environmental management practices or the allocation of public, productive and culturally valuable resources.